Scouting around 1, 2, 3, 4‐Tetrahydrochromeno[3, 2‐c]pyridin‐10‐ones for Single‐ and Multitarget Ligands Directed towards Relevant Alzheimer's Targets. (4th September 2020) - Purgatorio, Rosa; Kulikova, Larisa N.; Pisani, Leonardo; Catto, Marco; de Candia, Modesto; Carrieri, Antonio; Cellamare, Saverio; De Palma, Annalisa; Beloglazkin, Andrey A.; Reza Raesi, Ghulam; Voskressensky, Leonid G.; Altomare, Cosimo D.
Abstract: A number of 1, 2, 3, 4‐tetrahydrochromeno[3, 2‐ c ]pyridin‐10‐one derivatives have been synthesized and screened against different targets involved in the onset and progression of Alzheimer's disease (AD), such as acetyl‐ and butyrylcholinesterase (AChE and BChE), monoamine oxidases A and B (MAO A and B), aggregation of β‐amyloid (Aβ) and reactive oxygen species (ROS) production. Derivatives 1 c, 3 b, 4 and 5 a showed multifaceted profiles of promising anti‐AD features and returned well‐balanced multitargeting inhibitory activities. Moreover, compound 1 f, a potent and selective human MAO B inhibitor (IC50 =0.89 μM), proved to be a safe neuroprotectant in a human neuroblastoma cell line (SH‐SY5Y) by improving viability impaired by Aβ1–42 and pro‐oxidant insult. Furthermore, structure–activity relationships (SARs) and docking models were derived in order to assist further hit‐to‐lead optimization stage. Abstract : On target(s) : Different 1, 2, 3, 4‐tetrahydrochromeno[3, 2‐ c ]pyridin‐10‐ones have been synthesized and tested for their activity towards specific enzymes (AChE, BChE, MAO A and B) and targets (aggregation of Aβ and ROS production) related to Alzheimer's disease. Some compounds showed balanced multitargeting inhibitory effect, but one was a potent and selective human MAO B inhibitor with a neuroprotectant profile against Aβ1–42 and H2 O2 .